Fundamental right to secrecy and inviolability of communications: comparative analysis of its meaning and content - Velásquez Meléndez, Raffo (2025)
The author conducts a thorough analysis of the fundamental right to the secrecy and inviolability of communications from a jurisprudential, doctrinal, and legislative perspective, taking into account the challenges posed by technological advancements. The author asserts that this constitutional right ensures the protection of communications against arbitrary interferences, particularly in a context where the widespread use of the internet and mobile devices has heightened the risk of privacy infringements. Furthermore, the author contends that any restriction on this right is only permissible in exceptional circumstances, subject to prior judicial authorization and strict adherence to the principle of legality.In substantiating the study, the author draws upon constitutional provisions, international human rights instruments, and comparative law, all of which recognize this right as a cornerstone of the rule of law. Moreover, it is underscored that any limitation on this fundamental guarantee must be expressly prescribed by law, adhere to the principles of necessity and proportionality, and be subject to rigorous judicial scrutiny.